Phytosphingosine is a novel activator of GPR120. (24th January 2018) - Nagasawa, Tomotaka; Nakamichi, Hikaru; Hama, Yoichiro; Higashiyama, Shigeki; Igarashi, Yasuyuki; Mitsutake, Susumu
Abstract: GPR120 is a receptor for long chain fatty acids and is expressed in small intestinal endocrine cells, L cells and adipose tissue. Activation of GPR120 promotes the secretion of incretin GLP-1, which is known to have effects on anti-metabolic syndrome. As such, GPR120 is a potential target of pharmaceuticals for type II diabetes. In this study, we performed ligand-screening for GPR120 on glycero- and sphingo-type lipids and their derivatives using a Transforming Growth Factor α-shedding assay. We found that phytosphingosine (PHS) activates GPR120 in a manner comparable to the natural ligand α-linolenic acid (ALA) and superior to that of the synthetic ligand GW9508. The IC50 value of PHS was 33.4 μM, of ALA was 31.0 μM and of GW9508 was 41.7 μM. Additionally, PHS-induced activation of GPR120 was inhibited by the specific antagonist AH7614. Many of the natural or synthetic ligands found thus far are compounds with carboxyl groups. However, PHS does not possess a carboxyl group, suggesting that its manner of interaction with GPR120 may be significantly different from that of other ligands. Since PHS is rich in the plasma membrane of yeast, our results imply that PHS found in fermented food could have effects on anti-diabetes through activation of GPR120.